"I've Risen Up From the Ashes That I Created": Record Clearance and Gendered Narratives of Self-Reinvention and Reintegration. (April 2019) - Chen, Elsa Y.; Adams, Ericka B.
Record clearance allows some individuals to redesignate or remove certain minor convictions from their criminal records. This interview-based study finds that both men and women seek opportunities for personal gain through record clearance, but women are more motivated by moral and religious influences and concern about reputation. Women are also more likely than men to acknowledge personal flaws, and to desire to replace criminal identities with law-abiding identities. As women redefine their identities, caregiving is especially important as a personal obligation and professional aspiration. Record clearance is particularly compatible with women's motivations, willingness to change, and personal and professional goals.